2002
DOI: 10.1017/s0267190502000107
|View full text |Cite
|
Sign up to set email alerts
|

10. Teacher-Student Interaction and Language Learning

Abstract: This chapter reviews literature on recent developments in teacher-student interaction and language learning. Based on a sociocultural perspective of language and learning, the studies are drawn from three types of classrooms: first language classrooms; second language classrooms, which include contexts in which the language being learned in the classroom is also the language of the community; and foreign language classrooms. Foreign language learning contexts are those in which exposure to and opportunities fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
97
0
7

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(114 citation statements)
references
References 0 publications
4
97
0
7
Order By: Relevance
“…The recent history of responses to the IRF pattern reveals a growing interest in the ways in which this pervasive structure might be harnessed to positive effect in the language classroom by exploiting the possibilities of the third part of the sequence, a position that represents a considerable advance on the original response to its presence, which focussed on the first part (for a useful overview of recent research in this area, see Hall and Walsh 2002). This earlier approach trusted to the transformative power of open and ‗genuine' questions, as opposed to those which were closed and for display purposes only, but an examination of such avowedly ‗communicative' classroom interaction by Nunan (1987) revealed that it did nothing to change the inhibiting realities of teacher-controlled interaction.…”
Section: New Ways With the Irf Patternmentioning
confidence: 99%
“…The recent history of responses to the IRF pattern reveals a growing interest in the ways in which this pervasive structure might be harnessed to positive effect in the language classroom by exploiting the possibilities of the third part of the sequence, a position that represents a considerable advance on the original response to its presence, which focussed on the first part (for a useful overview of recent research in this area, see Hall and Walsh 2002). This earlier approach trusted to the transformative power of open and ‗genuine' questions, as opposed to those which were closed and for display purposes only, but an examination of such avowedly ‗communicative' classroom interaction by Nunan (1987) revealed that it did nothing to change the inhibiting realities of teacher-controlled interaction.…”
Section: New Ways With the Irf Patternmentioning
confidence: 99%
“…786-788;Hall & Walsh, 2002;Thoms, 2012, pp. 511-513; for reviews of more dialogist treatment of IRF).…”
Section: Discussion Of Indingsmentioning
confidence: 99%
“…Chaudron, 1988;Ellis, 2008, pp. 775-835;Hall & Walsh, 2002;Nunan, 1991Nunan, , 2005Thoms, 2012), in all of which theoretical and methodological plurality of research is re lected.…”
Section: Research On Classroom Interactionmentioning
confidence: 99%
“…All the excerpts above demonstrate that through interaction with each other, teachers and students constructed a common body of knowledge (Hall & Walsh, 2002). Clearly, as the interactions take place within instructional contexts, they are elicited by teachers (Ralston, 2004).…”
Section: Teachers-students Interactionmentioning
confidence: 99%